Ideologia, hegemonia e opinião pública: As contribuições de Gramsci à criminologia crítica - Budó, Marília de Nardin (2015)
From a critical evaluation of some of the main findings of critical criminology, this study aims to examine how the Marxist based contribution of Gramsci on hegemony can help in understanding the process of discursive legitimacy of the criminal justice system. It is a literature review that confronts different concepts of the Marxist tradition to understand how the diffusion of a critical counter-discourse can help in overcoming the violence of penal system. The system is divided into three parts. At first, it seeks to discuss some of the instrumental concepts on the proposed analysis from the work of Gramsci and his commentators. Then, it seeks to understand the constitutive nature of discourse about crime and its dialectical overcoming, from critical criminology. The third part discusses the need to complexify the concept of public opinion, especially questioning the results of public opinion polls often published and whose main themes are criminal matters. When relativized these polls because of methodological and conceptual issues, it is possible to identify an important area for insertion of counter-hegemonic discourse about the system.